In your own words 1. - Green, Joan M. (New York Holt Rinehart and Winston, 1981)
In your own words is a collection of stories, poems, plays, and articles presented in five units, each of which a different theme. "In your own words" offers you many opportunities to speak and to write.
Keywords: Science